2020
DOI: 10.1007/s00421-020-04431-4
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent versus continuous enteral nutrition attenuates increases in insulin and leptin during short-term bed rest

Abstract: Purpose To compare endocrine responses to intermittent vs continuous enteral nutrition provision during short-term bed rest. Methods Twenty healthy men underwent 7 days of bed rest, during which they were randomized to receive enteral nutrition (47%E as carbohydrate, 34%E as fat, 16%E as protein and 3%E as fibre) in a continuous (CONTINUOUS; n = 10; 24 h day −1 at a constant rate) or intermittent (INTERMITTENT; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…International guidelines [ 19 ] recommend the use of continuous feeding rather than intermittent boluses due to the lower incidence of side effects such as diarrhea; however, despite a strong consensus the grade of the recommendation is low, mainly because of the limited sample size and heterogeneity of the populations included, and the lack of proven benefits in other outcome measures. Indeed, the debate about the best strategy to deliver enteral feeding has grown in the last years, based on the concept that an intermittent pattern could better mimic the normal daily life feeding pattern [ 63 ], and on reports that continuous enteral feeding might improve the achievement of target nutrition requirements as compared to an intermittent pattern [ 64 ]. A recent systematic review which included 19 studies that compared the two approaches found both results in favor of a continuous pattern (such as lower gastric residuals and less need for prokinetics), and in favor of an intermittent one (i.e., better digestive tract colonization, lower constipation and less evidence of tracheal aspiration of gastric contents), and confirmed that the current level of evidence is not sufficient to provide clear indications on which approach should be preferred [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines [ 19 ] recommend the use of continuous feeding rather than intermittent boluses due to the lower incidence of side effects such as diarrhea; however, despite a strong consensus the grade of the recommendation is low, mainly because of the limited sample size and heterogeneity of the populations included, and the lack of proven benefits in other outcome measures. Indeed, the debate about the best strategy to deliver enteral feeding has grown in the last years, based on the concept that an intermittent pattern could better mimic the normal daily life feeding pattern [ 63 ], and on reports that continuous enteral feeding might improve the achievement of target nutrition requirements as compared to an intermittent pattern [ 64 ]. A recent systematic review which included 19 studies that compared the two approaches found both results in favor of a continuous pattern (such as lower gastric residuals and less need for prokinetics), and in favor of an intermittent one (i.e., better digestive tract colonization, lower constipation and less evidence of tracheal aspiration of gastric contents), and confirmed that the current level of evidence is not sufficient to provide clear indications on which approach should be preferred [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, intermittent feeding could reduce feeding intolerance, through beneficial effects on gastrointestinal hormones and by enhancing splanchnic blood flow [139,140]. Moreover, intermittent feeding could improve GI motility and nutrient (amino acid) uptake as a result of pulsatile changes in GI hormones such as ghrelin, cholecystokinin, glucagon-like peptide-1 and peptide YY [91,92,139,141]. However, the effect of intermittent feeding/fasting on entero-hormonal response has not yet been investigated in the ICU setting, adult nor paediatric.…”
Section: Gastro-intestinal Intolerancementioning
confidence: 99%
“…Hal ini sejalan dengan penelitian Sjulin et al, (2020) bahwa dinamika glukosa-insulin pada pasien kritis yang membutuhkan infus insulin untuk mempertahankan konsentrasi glukosa antara 140-180 mg/dl dengan pemberian nutrisi melalui metode intermittent feeding dapat menurunkan kebutuhan insulin dibandingkan dengan continuous. Kesinergisan dinamika antara glukosa-insulin ini didukung dalam penelitian Gonzalez et al, (2020) yang menyatakan rasio plasma insulin-to-glukagon tetap stabil selama istirahat di tempat tidur dengan intermittent, tetapi meningkat dengan continuous sehingga pada hari ke-6 dan 7, rasio insulin-to-glukagon plasma lebih rendah intermittent dibandingkan continuous. Pemberian nutrisi dengan metode intermittent feeding hampir mirip dengan metode sequential feeding baik waktu, durasi dan siklus pemberian nutrisinya.…”
Section: Pembahasanunclassified